2010
DOI: 10.1007/s10265-010-0385-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a nitrate-independent function of the nitrate sensor NRT1.1 in Arabidopsis thaliana

Abstract: NRT1.1 is a putative nitrate sensor and is involved in many nitrate-dependent responses. On the other hand, a nitrate-independent function of NRT1.1 has been implied, but the clear-cut evidence is unknown. We found that NRT1.1 mutants showed enhanced tolerance to concentrated ammonium as sole N source in Arabidopsis thaliana. This unique phenotype was not observed in mutants of NLP7, which has been suggested to play a role in the nitrate-dependent signaling pathway. Our real-time PCR analysis, and evidence fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
58
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 29 publications
2
58
0
Order By: Relevance
“…Recently, we have revealed that knockout mutants of NRT1.1 show enhanced tolerance to ammonium and/or low pH conditions in the absence of nitrate. 3 This observation directly suggests the existence of a nitrateindependent function of NRT1.1. In this addendum, putative mechanisms for this observation are discussed and prospective experimental approaches are suggested as below.…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…Recently, we have revealed that knockout mutants of NRT1.1 show enhanced tolerance to ammonium and/or low pH conditions in the absence of nitrate. 3 This observation directly suggests the existence of a nitrateindependent function of NRT1.1. In this addendum, putative mechanisms for this observation are discussed and prospective experimental approaches are suggested as below.…”
mentioning
confidence: 79%
“…3 Recently, some components related to the primary nitrate response have been determined. 8 Therefore, altered responses of these components may be related to the ammonium/low pH tolerance in the NRT1.1 mutants, although chl1-9, which has a normal primary nitrate response at least via NRT1.1, shows the tolerance.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…If correct, this model implies that manipulation of the nutrient sensing systems in the roots will affect the response of shoot growth to changes in nutrient availability. Interestingly, the NRT1.1 NO 3 − transceptor, which participates in the NO 3 − regulation of LR growth in A. thaliana (see above section), has recently been shown to also modulate shoot growth as a function of the N source (Hachiya et al 2011). However, there is no evidence yet that a putative role of NRT1.1 in the regulation of shoot growth is due to modified root-to-shoot CK signalling.…”
Section: Slowing Down Of Shoot Growthmentioning
confidence: 99%